Profiling shared e-scooter users : Environmental sustainability considerations - Rauhala, Veera (My University, 2024)
The shared electric scooter (e-scooter) rental business, which began in the United States in 2017, has gained exceptionally high popularity. E-scooters are suggested to have the potential to reduce private car usage, and they are hoped to be one solution in making urban transportation more environmentally sustainable. However, e-scooters have also faced significant criticism; the lack of regulation has caused numerous problems. In contemplating the role of e-scooters in future sustainable urban mobility, it is essential to better understand their users and environmental impacts. The purpose of this study is to identify user groups among e-scooter users and to examine how the environmental friendliness of their actions varies among different user groups. Additionally, the study investigates users' willingness to pay extra for environmentally friendlier e-scooter services. The study is quantitative, and data was collected through an online survey of shared electric scooter users in the summer of 2023. Variables were extracted from previous literature and combined using exploratory factor analysis (EFA). User profiles were identified employing latent profile analysis (LPA). Subsequently, the environmental friendliness of different user profiles was qualitatively assessed. LPA identified five distinct user groups: 1) frequent commuters, 2) car substituters, 3) frequent leisure users, 4) occasional leisure riders, and 5) indifferent leisure riders. Car replacement among users was low, which can be attributed to the fact that only 12.5% of respondents had a car in their household. Users reported primarily replacing walking, cycling, and public transportation, which are almost always a lower-emission mode of transport compared to e-scooters. Only the group replacing car usage showed potential for achieving environmental benefits through e-scooter usage. Groups 3 and 5 are likely to have a negative environmental impact with their electric scooter usage, while the overall environmental impact of groups 1 and 4 could not be assessed due to the limitations of the study. There was very little willingness to pay extra for more environmentally friendly e-scooters in all groups. The study shows that the potential environmental benefits of electric scooters are limited to only one user group, which does not use e-scooters very actively. Therefore, cities and operators could collaborate to develop incentives for users replacing car usage to use electric scooters for daily work and school commutes. An increase in car replacement would be a significant improvement for the system's environmental friendliness, as opportunities to reduce emissions from manufacturing are limited. However, literature emphasizes that the ways in which modes of transportation are replaced depend heavily on local factors, leading to variation in the environmental friendliness of electric scooters between cities. This study increases awareness of shared electric scooter users, their motives and behaviors, and the environmental impacts of different usage patterns. It also identifies topics for further research, which can deepen the understanding of e-scooter users, support creation of incentives for more environmentally friendly usage, and inform decision-makers who plan for sustainable urban mobility.

Vuonna 2017 Yhdysvalloissa alkanut sähköpotkulautojen vuokraustoiminta on saanut poikkeuksellisen suurta suosiota. Sähköpotkulaudoilla on arvioitu olevan potentiaalia vähentää yksityisautoilua, ja niiden on toivottu olevan yksi ratkaisu kaupunkiliikenteen kehittämisessä ympäristön kannalta kestävämmäksi. Potkulautoja on kuitenkin myös kritisoitu rankasti, ja niiden sääntelyn puute on aiheuttanut monia ongelmia. Pohdittaessa yhteiskäyttöisten sähköpotkulautojen roolia osana tulevaisuuden kestävää kaupunkiliikkuvuutta on olennaista ymmärtää niiden käyttäjiä ja ympäristövaikutuksia paremmin. Tämän tutkimuksen tarkoituksena on selvittää, millaisia käyttäjäryhmiä yhteiskäyttöisten sähköpotkulautojen käyttäjistä voidaan erotella, ja miten eri käyttäjäryhmien toiminta eroaa ympäristöystävällisyyden suhteen. Lisäksi tutkimus tarkastelee käyttäjien halukkuutta maksaa lisää ympäristöystävällisemmästä sähköpotkulautojen vuokrauspalvelusta. Tutkimus on kvantitatiivinen, ja data kerättiin verkkokyselynä yhteiskäyttöisten sähköpotkulautojen käyttäjiltä kesällä 2023. Muuttujien valinnassa hyödynnettiin aiempaa kirjallisuutta, ja ne yhdistettiin summamuuttujiksi eksploratiivisen faktorianalyysin (EFA) tulosten pohjalta. Käyttäjäprofiilit muodostettiin käyttäen latent profile analysis (LPA) -metodia. Tämän jälkeen eri käyttäjäprofiilien ympäristöystävällisyyttä arvoitiin kvalitatiivisesti. LPA erotteli viisi toisistaan eroavaa käyttäjäryhmää: 1) aktiiviset työmatkaajat, 2) autoilun korvaajat, 3) aktiiviset vapaa-ajan käyttäjät, 4) satunnaiset vapaa-ajan käyttäjät ja 5) välinpitämättömät vapaa-ajan käyttäjät. Auton korvaus käyttäjien keskuudessa oli matalaa, jota kuitenkin selittää se, että vain 12,5 prosentilla vastaajista oli auto kotitaloudessaan. Eniten käyttäjät raportoivat korvaavansa sähköpotkulaudoilla kävelyä, pyöräilyä ja julkista liikennettä, jotka ovat lähes aina sähköpotkulautoja vähäpäästöisempiä liikennemuotoja. Ainoastaan autoilua korvaavalla käyttäjäryhmällä voitiin havaita potentiaalia siihen, että sähköpotkulautojen käytöllä saavutettaisiin hyötyjä ympäristön kannalta. Ryhmät 3 ja 5 aiheuttavat sähköpotkulautojen käytöllään todennäköisesti negatiivisen ympäristövaikutuksen, kun taas ryhmien 1 ja 4 käytön kokonaisvaikutusta ympäristöön ei tutkimuksen rajallisuuden vuoksi voitu arvioida. Halukkuutta maksaa lisää ympäristöystävällisemmistä sähköpotkulaudoista oli hyvin vähän kaikissa ryhmissä. Tutkimus osoittaa, että sähköpotkulautojen potentiaalinen ympäristöhyöty rajoittuu vain yhteen käyttäjäryhmään, joka ei aja sähköpotkulaudoilla kovin aktiivisesti. Siksi kaupungit ja operaattorit voisivatkin kehittää yhdessä kannusteita autoilua korvaaville käyttäjille kulkea päivittäisiä työ- ja koulumatkoja sähköpotkulaudalla. Autoilun korvaamisen lisääntyminen olisi merkittävä parannus järjestelmän ympäristöystävällisyydelle, sillä mahdollisuudet vähentää potkulautojen valmistuksessa syntyviä päästöjä ovat rajalliset. Kirjallisuudessa kuitenkin korostuu, että tavat korvata kulkumuotoja riippuvat paljon paikallisista tekijöistä, ja siksi myös sähköpotkulautojen ympäristöystävällisyydessä esiintyy kaupunkien välistä vaihtelua. Tämä tutkimus lisää tietoisuutta sähköpotkulautojen käyttäjistä, heidän motiiveistaan ja tavoistaan sekä erilaisen käytön ympäristövaikutuksista. Se myös tunnistaa aiheita jatkotutkimukselle, jonka avulla voidaan ymmärtää syvemmin sähköpotkulautojen käyttäjiä, luoda kannustimia ympäristöystävällisemmälle käytölle ja tehdä päätöksiä sähköpotkulautojen roolista tulevaisuudessa.
Keywords: shared e-scooters, micromobility, environmental sustainability, life cycle assessment, user profiles, yhteiskäyttöiset sähköpotkulaudat, mikroliikkuvuus, ympäristöllinen kestävyys, elinkaarianalyysi, käyttäjäprofiilit